2018
DOI: 10.1534/genetics.117.1119
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Two H3K36me3 Histone Methyltransferases Set2 and Ash1 in Fusarium fujikuroi Unravels Their Different Chromosomal Targets and a Major Impact of Ash1 on Genome Stability

Abstract: In this work, we present a comprehensive analysis of the H3K36 histone methyltransferases Set2 and Ash1 in the filamentous ascomycete In, one single methyltransferase, Set2, confers all H3K36 methylation, while there are two members of the Set2 family in filamentous fungi, and even more H3K36 methyltransferases in higher eukaryotes. Whereas the yeast Set2 homolog has been analyzed in fungi previously, the second member of the Set2 family, designated Ash1, has not been described for any filamentous fungus. West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 88 publications
(132 reference statements)
4
87
1
Order By: Relevance
“…C). In contrast, the in loco integration of the point‐mutated variant SET1 H1191K , in which the catalytically active histidine of the SET domain has been mutated to a lysine residue (Tanaka et al ., ; Janevska et al ., ), did not complement as expected (Fig. C).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…C). In contrast, the in loco integration of the point‐mutated variant SET1 H1191K , in which the catalytically active histidine of the SET domain has been mutated to a lysine residue (Tanaka et al ., ; Janevska et al ., ), did not complement as expected (Fig. C).…”
Section: Resultssupporting
confidence: 72%
“…The WT, Δ set1 , Δ kdm5 and OE:: KDM5 mutants were grown in liquid ICI medium with 60 mM Gln for 3 days. Western blot detection of K4‐methylated H3 proteins in a whole‐protein extract was done as described elsewhere (Janevska et al ., ). The following primary antibodies were used (Active Motif, La Hulpe, Belgium): anti‐H3K4me1 (#39298; 1:10 000), anti‐H3K4me2 (#39141; 1:10 000), anti‐H3K4me3 (#39159; 1:10 000) and anti‐H3 C‐terminal (#39163; 1:10 000).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…). Such phenotypic changes are consistent with defective sexual development in methyltransferases knockout mutants in Fusarium fujikuroi (Janevska et al ., ) and Magnaporthe oryzae (Pham et al ., ). In recent years, several studies have shown that acetylation of histones and non‐histones regulates growth and development in various fungi, such as F. graminearum , M. oryzae and C. albicans .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that HMTs include many subtypes. 27,28 We specifically examined G9α-HMT, which is closely related to cardiac development and expressed in the heart. Western blotting analysis confirmed that the level of G9α was significantly lower in alcohol-treated mice than in control animals and showed that alcohol caused histone H3K9me3 hypomethylation.…”
Section: Discussionmentioning
confidence: 99%